VELVET REVOLUTION IN ARMENIA AND ITS INFLUENCE ON STATE POLICY: SELECTED ASPECTS - MIARKA, Agnieszka (CENTRAL ASIA AND THE CAUCASUS, 2019)
The aim of the article is to analyze and characterize the 2018 Velvet Revolution in Armenia and to present its influence on the politics of this country. The first part of the article is devoted to pointing out the most important factors that led to the mass protests in Armenia, such as the weakness and corruption of political elites, monopolization of power structures by one party, inefficiency of foreign policy, or the constitutional amendment of 2015. The emphasis was placed on the political determinants of the state political crisis. The course of events during the revolution is subsequently presented, emphasizing the priority role held by the opposition leader Nikol Pashinyan. The paper concludes with the enumeration of the most important transformations in Armenia’s politics, which were initiated after the My Step bloc came to power, and Pashinyan took over the position of Prime Minister.